A Review of The Role of Graphene in Enhancing Concrete Performance by Increasing Electrical Conductivity and Enabling Its Innovative Applications (Development Engineering Conferences Center Articles Database, 2025)
This article presents a comprehensive review of the literature regarding the applications of graphene additives in concrete, focusing on the enhancement of electrical conductivity. As concrete is traditionally an insulator, the integration of graphene has emerged as a promising solution to improve its electrical properties, thereby enabling innovative applications in smart infrastructure and self-sensing systems. The review categorizes various studies that explore the effects of graphene on the mechanical and electrical characteristics of concrete, highlighting advancements in material performance, durability, and functionality. Additionally, the article discusses the environmental impacts associated with the incorporation of graphene in concrete, including potential reductions in carbon emissions and resource consumption. The findings underscore the transformative potential of graphene-enhanced concrete in addressing contemporary challenges in construction and sustainability.